Peningkatan Kesadaran Stunting Berbasis Edukasi-Demonstrasi Pangan Lokal di Posyandu Tomeko-A - Magdarita Riwu; Yohana Febriani Putri Peu Patty; Jasvidianto Chriza Kotta; Matias Nataniel Kolobani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This Community Service Program aimed to enhance awareness of early stunting prevention, promote the use of locally available nutrient-rich foods, and encourage balanced and sustainable dietary practices. Methodology: The program was carried out at Posyandu Tomeko A, East Penfui Village, using a participatory educational approach that combined counselling on the importance of iron intake during pregnancy with demonstrations of processing red spinach into nutritious foods. A 5-point Likert-scale satisfaction questionnaire was administered after the activity, and data were analyzed descriptively. Results: Thirty participants mostly adult women and adolescent girls aged ?21 years took part in the program and showed strong enthusiasm, particularly on risk factors and dietary challenges. Evaluation of 300 responses showed very positive feedback, with 62.3% “Very Satisfied,” 36.0% “Satisfied,” yielding a mean score of 4.61. Overall, the program effectively enhanced participants’ understanding of the importance of iron intake during the first 1,000 days of life in preventing stunting. Conclusions: The counseling program effectively improved community awareness through structured nutrition education, demonstrations of local iron-rich foods, and leaflet distribution. High satisfaction scores indicate that the materials were relevant and well-received. Limitations: No pre–post testing was conducted, the sample was small, and no follow-up assessment occurred. Contributions: The program provides practical guidance for families and posyandu cadres and demonstrates that participatory education can motivate communities to act as agents of change in stunting prevention.